Clarithromycin-based triple therapy for Helicobacter pylori treatment in peptic ulcer patients - Guilherme Eduardo Gonçalves Felga; Fernando Marcuz Silva; Ricardo C. Barbuti; Tomás Navarro–Rodriguez; Schlioma Zaterka; Jaime Natan Eisig (2010)
Introduction: The scheme proton pump inhibitor/amoxicillin/clarithromycin (PPI/AC) is still the first-line treatment for Helicobacter pylori (H. pylori) infections despite evidence suggesting its failure in up to 20% to 30% of patients. Methodology: This study involved 493 patients who were prescribed omeprazole (20 mg twice a day) or another proton pump inhibitor in equivalent dosage, amoxicillin (1 g twice a day), and clarithromycin (500 mg twice a day) for seven days. Efficacy was determined by negative urease test and absence of H. pylori on gastric biopsy samples twelve weeks after the end of treatment. Safety was defined according to the adverse effects reported. Mean age of the patients was (± SD) 48.96 ± 13, and demographic and clinical data were recorded for correlation with treatment outcomes. Results: Out of 493 patients, 316 (64.1%) presented duodenal ulcer, 111 (22.5%) gastric ulcer, and 66 (14.4%) simultaneous gastric and duodenal ulcers. Additionally, 267 (54.2%) patients had at least one risk factor for peptic ulcer disease, smoking being the most common (99 [36.5%]). Successful eradication was achieved in 408 patients. The eradication rates per protocol, and according to the intention to treat, were 88.8% and 82.7%, respectively. Of 164 (35.5%) patients who presented adverse effects, 100 (61%) reported them as mild and only six (3.7%) patients had to discontinue treatment. Previous use of tobacco and non-steroid anti-inflammatory drugs was the only risk factor for treatment failure (P 0.00). Conclusion: PPI/AC is still a valuable and remarkably tolerable option for first-line H. pylori eradication in Brazil.